Integration of Mangunan Tourism Information Through Interactive Digital Tourist Maps - Utami, Yenni Sri; Simanjuntak, Oliver Samuel (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to integrate tourism information in the Mangunan area into an interactive digital tourist map application based on the Geographic Information System (GIS). The goal is to help tourists get tourist information in one comprehensive application. This GIS-based map also helps tourism managers promote their tour packages. In addition, the Bantul Regency Government is assisted in promoting tourism in Bantul Regency. The method used is the Waterfall application development method. The results obtained indicate that this GIS-based interactive digital map can overcome several problems of distribution of tourist information in the Mangunan area. From the results of expert reviews in application development, this map is considered user-friendly.